Unique clade of alphaproteobacterial endosymbionts induces complete cytoplasmic incompatibility in the coconut beetle - Takano, Shun-ichiro (Proc Natl Acad Sci U S A, 2017)
Maternally inherited bacterial endosymbionts in arthropods manipulate host reproduction to increase the fitness of infected females. Cytoplasmic incompatibility (CI) is one such manipulation, in which uninfected females produce few or no offspring when they mate with infected males. To date, two bacterial endosymbionts, Wolbachia and Cardinium, have been reported as CI inducers. Only Wolbachia induces complete CI, which causes 100% offspring mortality in incompatible crosses. Here we report a third CI inducer that belongs to a unique clade of Alphaproteobacteria detected within the coconut beetle, Brontispa longissima. This beetle comprises two cryptic species, the Asian clade and the Pacific clade, which show incompatibility in hybrid crosses. Different bacterial endosymbionts, a unique clade of Alphaproteobacteria in the Pacific clade and Wolbachia in the Asian clade, induced bidirectional CI between hosts. The former induced complete CI (100% mortality), whereas the latter induced partial CI (70% mortality). Illumina MiSeq sequencing and denaturing gradient gel electrophoresis patterns showed that the predominant bacterium detected in the Pacific clade of B. longissima was this unique clade of Alphaproteobacteria alone, indicating that this endosymbiont was responsible for the complete CI. Sex distortion did not occur in any of the tested crosses. The 1,160 bp of 16S rRNA gene sequence obtained for this endosymbiont had only 89.3% identity with that of Wolbachia, indicating that it can be recognized as a distinct species. We discuss the potential use of this bacterium as a biological control agent.